Potential predictive factors for pathologic complete response after the neoadjuvant treatment of rectal adenocarcinoma: a single center experience - Feryel Letaief (Cancer Biology & Medicine, 2017)
Objective : To assess the response rate of patients with rectal adenocarcinoma to neoadjuvant therapy and to identify the predictors of histological regression after neoadjuvant radiotherapy (RT) or concurrent chemoradiotherapy (CCRT). Methods : This study recruited 64 patients. The patients had resectable cancer of the lower and the middle rectum (T3/T4 and/or N+) without distant metastasis and received neoadjuvant RT or CCRT followed by radical surgery with total mesorectal excision (TME) between January 2006 and December 2011. The patients were classified into non-response (NR), partial response (PR), and pathologic complete response (pCR) based on the Dworak tumor regression grading system.Results : The median age of patients was 57 years (ranging from 22 to 85). A total of 24 patients were treated with neoadjuvant CCRT, whereas 40 patients were treated with RT alone. Abdominoperineal resection (APR) was performed on 29 patients (45%). Anterior resection with TME was performed on 34 patients (53%). One patient had local resection. Histologically, 12 (19%), 24 (73%), and 28 (44%) patients exhibited pCR, PR, and NR, respectively. Univariate analysis revealed that the predictors of tumor regression were as follows: the absence of lymph node involvement from initial imaging (cN0) (P=0.021); normal initial carcinoembryonic antigen (CEA) level (P=0.01); hemoglobin level ≥12 g/dl (P=0.009); CCRT (P=0.021); and tumor downstaging in imaging (P=0.001). Multivariate analysis showed that the main predictors of pCR were CT combined with neoadjuvant RT, cN0 stage, and tumor regression on imaging. Conclusions : Identifying the predictors of pCR following neoadjuvant therapy aids the selection of responsive patients for non-aggressive surgical treatment and possible surveillance.